Learning styles : Are they fact or fiction? - Waynne B. James; William E. Blank; Donna Morrison; Kourtland Koch; Arthur Shapiro; Len Schiaper; Marsha Tindell (Adult Education Research Conference, 1996)
As researchers attempt to identify and analyze the variety of factors that contribute to or inhibit the learning process, it is common to focus on elements external to the learner (e.g., teaching methods, classroom setting, curriculum development). Less research has focused on elements internal to the learner (e.g., the processes by which the learner perceives, interprets, stores, and recalls information). The various ways in which learners react to learning experiences, the learning environment, and related elements compose an individual’s learning style. Do Learning Styles Really Exist? Research Related to the Perceptual Learning Style Modality Research related to Cognitive and Affective Learning Style Modalities An Assessment of Learning Style Instruments for Adults What’s Needed?